Commentary on the Old Testament ; v. 7 - Keil, Johan Karl Friedrich, 1807-1888; Delitzsch, Franz Julius, 1813-1890; Martin, James (Grand Rapids, MI Eerdmans)
Contents : v. 7 : Isaiah / F. Delitzsch. Includes bibliographical references.
Reprinted 1975.
Keywords: Bible. O.T. -- commentaries